2020
DOI: 10.1177/1759720x20937966
|View full text |Cite
|
Sign up to set email alerts
|

Setting up distinctive outcome measures for each osteoarthritis phenotype

Abstract: Osteoarthritis (OA) is an evolving chronic joint disease with a huge global impact. Given the intricate nature of the etiopathogenesis and subsequent high heterogeneity in the clinical course of OA, it is crucial to discriminate between etiopathogenic endotypes and clinical phenotypes, especially in the early stages of the disease. In this sense, we propose that an OA phenotype should be properly assessed with a set of outcome measures including those specifically related to the main underlying pathophysiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 144 publications
0
14
0
2
Order By: Relevance
“…Nelson et al observed that baseline variables as BMLs, osteophytes, medial meniscal extrusion, and urine CTX-II were useful to identify progression OA phenotypes at 48 months, while WOMAC pain, lateral meniscal extrusion, and serum N-terminal pro-peptide of collagen IIA (PIIANP) were associated with non-progression phenotypes (Nelson et al, 2019). Establishing OA phenotypes and then setting up distinctive outcome measures for each phenotype is a way to organize more effective and stratified clinical trials in OA in future (Roman-Blas et al, 2020). For example, the synovitis features detected by MRI or ultrasound (US) have the potential to become the useful outcome measures and could be used in clinical trials of new drugs that target synovitis in OA patients with inflammatory phenotype.…”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nelson et al observed that baseline variables as BMLs, osteophytes, medial meniscal extrusion, and urine CTX-II were useful to identify progression OA phenotypes at 48 months, while WOMAC pain, lateral meniscal extrusion, and serum N-terminal pro-peptide of collagen IIA (PIIANP) were associated with non-progression phenotypes (Nelson et al, 2019). Establishing OA phenotypes and then setting up distinctive outcome measures for each phenotype is a way to organize more effective and stratified clinical trials in OA in future (Roman-Blas et al, 2020). For example, the synovitis features detected by MRI or ultrasound (US) have the potential to become the useful outcome measures and could be used in clinical trials of new drugs that target synovitis in OA patients with inflammatory phenotype.…”
Section: Expert Opinionmentioning
confidence: 99%
“…The OA patients in the progressed periods are potentially more responsive to interventions, and these patients might be recruited in DMOAD trials to assess the efficacy of a new drug in the future. Sensitive and valid biomarkers are expected to become useful tools to predict OA progression and understand mechanisms of progression (Roman-Blas et al, 2020). On the other hand, OA may only be retarded at early to mid-stages instead of established or advanced OA.…”
Section: Expert Opinionmentioning
confidence: 99%
“… 79 Moreover, to capture relevant changes, early or intermediate outcome measurements should be tailored to the clinical phenotypes of OA. 80 …”
Section: How Work Performed In Oa Phenotyping Might Impact Prp Therapmentioning
confidence: 99%
“…Через 6 мес соотношение между подгруппами N вибір адекватного лікування [4,19]. Встановлення фенотипів ОА, а потім встановлення відмінних показників результатів для кожного фенотипу -це спосіб організації більш ефективних та стратифікованих клінічних випробувань при ОА у майбутньому [23]. Наприклад, ознаки синовіту, виявлені за допомогою МРТ або ультразвукового дослідження (УЗД), потенційно можуть стати корисним показником результату і бути використані в клінічних випробуваннях нових препаратів, спрямованих на лікування синовіту у пацієнтів з ОА із запальним фенотипом.…”
Section: посттравматический остеоартроз эффективная комбинация нестероидных противовоспалительных препаратов и Sysadoa аа бурьянов тн омеunclassified
“…Очікується, що чутливі та дійсні біомаркери стануть корисними інструментами для прогнозування прогресування ОА та розуміння механізмів прогресування [23]. З іншого боку доведено, що ОА може бути загальмований лише на ранніх та середніх стадіях на відміну від пізніх або термінальних стадій ОА.…”
Section: посттравматический остеоартроз эффективная комбинация нестероидных противовоспалительных препаратов и Sysadoa аа бурьянов тн омеunclassified